Pengolahan Sampah Anorganik Menjadi Media Pembelajaran Bagi Guru TK/RA - M Khoiri; Harsono Harsono (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2018)
This service activity aims to help improve the understanding, knowledge and creativity of TK Nurul Iman and RA Assaadah teachers about their learning and development tools, learning media made from inorganic waste and their development, and the application of instructional media in the classroom according to themes / material to improve the quality of learning for teachers as educators. After this activity the results were an increase in understanding, knowledge, and creativity for teachers, the availability of goods/objects (in the form of learning media) and their application. The method of implementing this activity is packaged with workshops and direct practices (both in making and applying in class). Participants are grouped according to their respective classes and themes and given guidance on the implementation of activities. The evaluation was carried out before and after the activity to find out the improvement of basic skills until the end of the activity so that it was concluded that this activity provided added value to the teacher concerned. The criteria for the success of this activity can be viewed from the attendance of the participants, mastery of the material, the application of material for making learning media and demonstration activities on media use.